Fabrication of Lignin/poly(3-hydroxybutyrate) Nanocomposites with enhanced Properties via a Pickering Emulsion approach - Lugoloobi, Ishaq; Li, Xiang; Zhang, Yunchong; Mao, Zhiping; Wang, Bijia; Sui, Xiaofeng; Feng, Xueling (International journal of biological macromolecules, 2020)
The present-day world still demands for various commercially viable biosourced materials to replace the finite petroleum-derived polymers. Herein, lignin nanoparticles were homogeneously dispersed in the poly(3-hydroxybutyrate) (PHB) matrix via an economical, simple and environmentally friendly oil-in-water Pickering emulsion approach to form a nanocomposite with improved properties. The prepared lignin/PHB nanocomposites were investigated for their morphological, thermal, optical, rheological and mechanical properties. The lignin nanoparticles proved to be efficient nucleating agents for PHB in that they noticeably increased the crystallization rates of the polymer. PHB film containing 7% lignin demonstrated the optimum improvement in the tensile performance with 13.2% and 43.9% increase in tensile strength and Young's modulus, respectively. This upturn was ascribed to the uniform dispersion of the lignin nanoparticles and the formation of strong interfacial adhesion between the filler and the matrix due to hydrogen bonding interactions. Moreover, lower crystallinity, higher glass transition temperature, improved UV resistance/blocking and higher melt viscosity were achieved in the blends. The synergetic advancement in these properties may be of significant importance for the wider application of bio-sourced PHB in the packaging industry.
Keywords: Lignin; Dispersion; PHB; Particle-reinforcement